BRCA Testing by Single-Molecule Molecular Inversion Probes. (6th January 2020) - Neveling, Kornelia; Mensenkamp, Arjen R; Derks, Ronny; Kwint, Michael; Ouchene, Hicham; Steehouwer, Marloes; van Lier, Bart; Bosgoed, Ermanno; Rikken, Alwin; Tychon, Marloes; Zafeiropoulou, Dimitra; Castelein, Steven; et al.
Abstract: BACKGROUND: Despite advances in next generation DNA sequencing (NGS), NGS-based single gene tests for diagnostic purposes require improvements in terms of completeness, quality, speed, and cost. Single-molecule molecular inversion probes (smMIPs) are a technology with unrealized potential in the area of clinical genetic testing. In this proof-of-concept study, we selected 2 frequently requested gene tests, those for the breast cancer genes BRCA1 and BRCA2, and developed an automated work flow based on smMIPs. METHODS: The BRCA1 and BRCA2 smMIPs were validated using 166 human genomic DNA samples with known variant status. A generic automated work flow was built to perform smMIP-based enrichment and sequencing for BRCA1, BRCA2, and the checkpoint kinase 2 ( CHEK2 ) c.1100del variant. RESULTS: Pathogenic and benign variants were analyzed in a subset of 152 previously BRCA-genotyped samples, yielding an analytical sensitivity and specificity of 100%. Following automation, blind analysis of 65 in-house samples and 267 Norwegian samples correctly identified all true-positive variants (>3000), with no false positives. Consequent to process optimization, turnaround times were reduced by 60% to currently 10–15 days. Copy number variants were detected with an analytical sensitivity of 100% and an analytical specificity of 88%. CONCLUSIONS: smMIP-based genetic testing enables automated and reliable analysis of the coding sequences of BRCA1 and BRCA2 . The use of single-molecule tags, double-tiled targeted enrichment, and capturing and sequencing in duplo, in combination with automated library preparation and data analysis, results in a robust process and reduces routine turnaround times. Furthermore, smMIP-based copy number variation analysis could make independent copy number variation tools like multiplex ligation-dependent probes amplification dispensable.